Population-based study: socio-demographic and health profile of older adults [Estudo de base populacional: perfil sociodemográfico e de saúde em idosos] [Estudio de base poblacional: perfil sociodemográfico y de salud en ancianos] - Álvaro da Silva Santos; Joilson Meneguci; Lúcia Marina Scatena; Marta Regina Farinelli; Mariana Campos de Sousa; Renata Damião (Revista Enfermagem UERJ, 2018)
Objective: to identify the sociodemographic and health profile of older adults in municipalities of the Uberaba Health Region in Minas Gerais, Brazil. Method: in this cross-sectional, population-based study, the Mini-Mental State Examination, a demographic and health profile instrument, the Mini Nutritional Assessment, WHOQOL-BREF and WHOQOL-OLD were applied to 3430 older adults in 24 cities, between 2012 and 2013. Data were analyzed using SPSS version 20.0. Results: female (61.5%), 60 to 69 years old (52.6%), no schooling or incomplete basic schooling (83.5%), income of one minimum wage or less (39.7%), pensioners (80.7%), mean 3.17 illnesses (SD = 1.92), use of 2.47 medicines (DP = 1.37), at risk for malnutrition (29.1%), overweight (62.9%), alcohol use (15.7%), smoking (15%), sedentary (43.1%), and with lowest quality of life scores in the environment domain (62.0%; DP = 13.2) and autonomy facet (66.8%; DP = 16.4). Conclusion: the study population was characteristically female, low-income, overweight, sedentary, had three diseases, and lowest quality of life scores in the environment domain and autonomy facet.